Modelling the interaction of transport system elements - Sivilevičius, Henrikas (Transport, 2011)
Economy and nonproductive sectors of each country could not function without a transport system (TS). Having analysed research works on the interaction of separate TS elements, it was identified that there is no common model for all types of interaction. TS consists of material (physical) objects: traffic participants and freight to be carried, a transportation process and operations’ control. TS classification scheme devised according to systematically selected criteria, showing that several criteria are often applied at the same time in official documents, is presented. Original TS physical elements’ interaction model with 6 interaction levels is presented as well. The model is suitable for all modes of transport. Six levels of interaction are distinguished: autointeraction of transport elements, the first level; TS elements’ interaction, the second level; TS elements’ interaction with external environment, the third level; interaction of transport modes, the fourth level; TS interaction with the country's economy and nonproductive sectors, the fifth level; and TS impact on the country's GAV (Gross Added Value), the sixth level. Properties and factors influencing on the results and parameters of interaction have been systematized. Levels and properties of interaction have been analyzed as well. To evaluate the importance of interaction levels to the parameters of the transportation process, the method of Analytic Hierarchy Process (AHP) has been recommended.First Published Online: 12 Apr 2011